Leaders and Leadership: An Overview of Abdul Rani Mahmud's Thoughts - Muhamad Tisna Nugraha; Muhammad Rahmatullah (Universitas Muhammadiyah Magelang, 2021)
From the perspective of an Islamic scholar from Pontianak, Abdul Rani Mahmud (1912 – 1993 AD), this study aims to reveal the character values that should be attached to leaders in carrying out their roles, duties, and functions. The main source for this study is a typed text by Abdul Rani Mahmud, which was analyzed using a qualitative method. According to the findings of this study, a leader is someone who genuinely wants to be the mouthpiece of the people he leads, and who sincerely wants to be able to fight for what has become a common goal and benefit. A leader's leadership character should include eight characteristics: 1) intelligence (fathonah), 2) trustworthiness, 3) fairness, 4) honesty (shidiq), 5) hard work (ikhtiar), 6) religiosity, 7) responsibility, and 8) populism.